There is no crime for those who have Christ : religious violence in the Christian Roman Empire - Gaddis, Michael, 1970- (Berkeley, Calif. ; London : University of California Press, 2005)
There is no crime for those who have Christ," claimed a fifth-century zealot, neatly expressing the belief of religious extremists that righteous zeal for God trumps worldly law. This book provides an in-depth and penetrating look at religious violence and the attitudes that drove it in the Christian Roman Empire of the fourth and fifth centuries, a unique period shaped by the marriage of Christian ideology and Roman imperial power.
What has the emperor to do with the church?" : persecution and martyrdom from Diocletian to Constantine -- "The God of the martyrs refuses you" : religious violence, political discourse, and Christian identity in the century after Constantine -- An eye for an eye : religious violence in donatist Africa -- Temperata severitas : Augustine, the state, and disciplinary violence -- "There is no crime for those who have Christ" : holy men and holy violence in the late fourth and early fifth centuries -- "The monks commit many crimes" : holy violence contested -- "Sanctify thy hand by the blow" : problematizing Episcopal power -- Non iudicium sed latrocinium : of Holy Synods and robber councils.
"A Joan Palevsky Book in Classical Literature."
Revision of the author's thesis (Ph. D.)--Princeton University, 1999.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Persecution; Violence -- Religious aspects -- Christianity; Church history -- 4th century; Church history -- 5th century; Martyrdom; Church history; Violence; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; HISTORY -- Ancient -- General; Church history; Martyrdom; Persecution; Violence -- Religious aspects -- Christianity; 300-499; Teologi -- Teologi; Electronic books